Defining social entrepreneurship = Eine Definition von Social Entrepreneurship - Jansen, Stephan A.; Richter, Saskia; Hahnke, Elisabeth; Achleitner, Ann-Kristin; Spiess-Knafl, Wolfgang; Volk, Sarah; Then, Volker; Mildenberger, Georg; Scheuerle, Thomas; Schmitz, Björn (Social Science Research Network, 2011)
The Mercator Research Network Zeppelin University - TU Munich - CSI Heidelberg analyzes the organization, communication, legitimacy and governance of social entrepreneurs. The underlying definition uses fourteen criteria to characterize social entrepreneurship and tries to differentiate between different phenomena.